2013
DOI: 10.7314/apjcp.2013.14.12.7271
|View full text |Cite
|
Sign up to set email alerts
|

Lack of any Association between Insertion/Deletion (I/D) Polymorphisms in the Angiotensin-converting Enzyme Gene and Digestive System Cancer Risk: a Meta-analysis

Abstract: were inconsistent, and a single study might be insufficient to detect a possible small effect of the polymorphism on digestive system cancer. We conducted a meta-analysis combining all eligible case-control studies to estimate the association between this polymorphism and digestive system cancer risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Our results did not show any association between ACE I/D polymorphism and CRC in each genetic models ( P  > 0.05). This is in accordance with meta-analysis conducted by Liu et al and Zhang et al [12,45]. …”
Section: Discussionsupporting
confidence: 93%
“…Our results did not show any association between ACE I/D polymorphism and CRC in each genetic models ( P  > 0.05). This is in accordance with meta-analysis conducted by Liu et al and Zhang et al [12,45]. …”
Section: Discussionsupporting
confidence: 93%
“…When differential expression of microRNAs was detected in plasma of patients with laryngeal squamous cell carcinoma, hsa-miR-19a-3p was confirmed as a potential early-detection marker for laryngeal squamous cell carcinoma (Ayaz et al 2013). Also, hsa-miR-19a-3p was texted in breast cancer grouped by clinicopathological subtypes (Liu et al 2013). Down-regulation of miR-181b promoted apoptosis by targeting CYLD in thyroid papillary cancer, and hsa-miR-19a-3p was detected and played an important role (Li et al 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Considering the multifactorial and heterogeneous nature of cancer, there is a necessity to establish a catalogue of driver genes or loci for each tumor type. As an extension of a recent meta-analysis by Liu et al, 31 we identified the source of the controls as a potential contributor to account for strong evidence of heterogeneity in this meta-analysis. Ruano-Ravina and colleagues have done a methodological comparison between populationbased and hospital-based controls on lung cancer risk, and highlighted obvious differences between the two sources of controls in risk estimates.…”
Section: Discussionmentioning
confidence: 97%